Maximum isometric tongue force in patients with obstructive sleep apnoea - Birk, Richard; Stuck, Boris; Maurer, Joachim T.; Schell, Angela; Müller, C. Emika; Kramer, Benedikt; Hoch, Stephan; Sommer, J. Ulrich (European archives of oto-rhino-laryngology and head & neck, 2021)
Obstructive sleep apnea (OSA) is a sleep disorder with a prevalence of 9-38%. The underlying pathology in OSA is a collapse of the upper airway. Especially in more severely affected patients, this collapse is often located at the level of the tongue base. Therefore, various implantable systems (anchors and ligament techniques) were developed to prevent or overcome this collapse. These systems are exposed to various forces. Different models have been developed to measure these forces and data comparing forces in healthy individuals with OSA patients are rare.
Published: 27 October 2020
Gesehen am 13.09.2021